Considerations on inhibition approaches for proinflammatory functions of ADAM proteases. (19th May 2017) - Dreymueller, Daniela; Ludwig, Andreas
Abstract: Proteases of the disintegrin and metalloproteinase (ADAM) family mediate the proteolytic shedding of various surface molecules including cytokine precursors, adhesion molecules, growth factors, and receptors. Within the vasculature ADAM10 and ADAM17 regulate endothelial permeability, transendothelial leukocyte migration, and the adhesion of leukocytes and platelets. In vivo studies show that both proteases are implicated in several inflammatory pathologies, for example, edema formation, leukocyte infiltration, and thrombosis. However, both proteases also contribute to developmental and regenerative processes. Thus, although ADAMs can be regarded as valuable drug targets in many aspects, the danger of severe side effects is clearly visible. To circumvent these side effects, traditional inhibition approaches have to be improved to target ADAMs at the right time in the right place. Moreover, the inhibitors need to be more selective for the target protease and if possible also for the substrate. Antibodies recognizing the active conformation of ADAMs or small molecules blocking exosites of ADAM proteases may represent inhibitors with the desired selectivities.